The use of Babadotan leaves (Ageratum conyzoides l) flour in ration on quail ration (Cortunix-cortunix Japonica) energy metabolism - Swasasi Sofi Makarim; Deden Sudrajat; Dede Kardaya (Bioculture Journal, 2026)
Background: Quails are livestock whose main products are eggs and meat. This plant is often referred to as a weed because its clinical benefits are not yet widely known to the public. The purpose of this study was to determine the effect of adding babadotan (Ageratum conyzoides L.) leaf meal on the metabolizable energy of quails (Coturnix coturnix japonica). The research was conducted at the Quail House, Arkan Quail Farm (Jl. Bebengket, Cihideung Village, Ciampea District, Bogor Regency, 16620). Methods: The study used a Completely Randomized Design (CRD) with four treatments: P0 = commercial feed without babadotan leaf meal (control), P1 = commercial feed with 1% babadotan leaf meal, P2 = commercial feed with 3% babadotan leaf meal, and P3 = commercial feed with 5% babadotan leaf meal. The observed variables included Apparent Metabolizable Energy (AME), Nitrogen-Corrected Apparent Metabolizable Energy (AMEn), total metabolizable energy consumption, and the AMEn/GE ratio. Findings: The results of this study showed that the addition of babadotan leaf meal (Ageratum conyzoides L.) in the diet significantly (P<0.05) affected the values of apparent metabolizable energy (AME) and nitrogen-corrected apparent metabolizable energy (AMEn), with a decrease observed in treatment R3 (diet containing 5% babadotan leaf meal). However, the results for metabolizable energy intake and the AMEn/GE ratio in quails (Coturnix coturnix japonica) were not significantly different or did not show a significant effect. Conclusion: The inclusion of babadotan leaf meal at a level of 5% in the diet can reduce the values of AME and AMEn. However, it did not significantly affect metabolizable energy intake or the AMEn/GE ratio. Novelty/Originality of this article: Therefore, the use of babadotan leaf meal in the diet is recommended only up to a concentration of 3%.